The experience of Facultad de Comercio, Administracion y Ciencias Sociales de Nuevo Laredo, Tamaulipas versus phenomenon of climate chance - Herrera-Izaguirre, Juan Antonio (Universidad Autónoma de Tamaulipas, 2011)
This paper discusses the phenomenon of climate change and its negative effects, it describes the experience and strategies of the Facultad de Comercio, Administración y Ciencias Sociales (Fcacs) in the fields of culture, education, environmental awareness, recycling and reforestation in response to this phenomenon. It also recognizes the importance of the subject “Environment and sustainable development” as the appropriate forum to begin to make this work.